2019
DOI: 10.1039/c8cs00595h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel bioelectronics

Abstract: Hydrogels have emerged as a promising bioelectronic interfacing material. This review discusses the fundamentals and recent advances in hydrogel bioelectronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1,227
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,455 publications
(1,305 citation statements)
references
References 218 publications
1
1,227
0
Order By: Relevance
“…Hydrogels are a class of viscoelastic materials with 3D networks and are able to absorb and retain a large amount of water . Hydrogels are commonly composed of chemically or physically cross‐linked hydrophilic polymers.…”
Section: Summary Of the Reports About Pva/pei‐based Composition And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are a class of viscoelastic materials with 3D networks and are able to absorb and retain a large amount of water . Hydrogels are commonly composed of chemically or physically cross‐linked hydrophilic polymers.…”
Section: Summary Of the Reports About Pva/pei‐based Composition And Tmentioning
confidence: 99%
“…The PVA/PEI copolymer has been widely used in antibacterial materials, biosensors, drug delivery vehicles, and a binder of Li‐ion battery, as summarized in Table 1 . These studies revealed that the PVA/PEI copolymer is biocompatible and stretchable.…”
Section: Summary Of the Reports About Pva/pei‐based Composition And Tmentioning
confidence: 99%
“…Adhesive materials play a significant role in industrial and biomedical fields, which have been widely applied into various applications, including soft robots, [1] wound dressing, [2,3] wearable devices, [4][5][6] and 3D printing [7,8] in water or oil. Up to now, intense endeavor has been devoted to revolutionizing adhesion science and technology for developing more promising applications.…”
Section: Introductionmentioning
confidence: 99%
“…Soft tactile sensors based on ionic charge injection will be not only an innovative try on the development of new sensing mechanism, but also significant to break boundaries between biological tissues and machines, because ionic charge injection is one of the currently adopted mechanisms to introduce ionic currents at tissue–electrode interfaces in bioelectronics . Here, we report an ultrasensitive ionic‐type tactile sensor with optimally designed structures, including a silver‐nanoparticles (Ag NPs)‐embedded hydrogel sandwiched by two copper electrodes.…”
Section: Introductionmentioning
confidence: 99%